Studi Perpindahan Panas pada Proses Pembakaran Briket Berbahan Dasar Pakis Hutan - Jusuf Haurissa; Mathinus Pembuaian (Jurnal Teknik Mesin, 2024)
There is an ongoing effort to develop and improve the quality of briquettes, which could become an alternative fuel source. This can be achieved by exploring the utilization of raw materials like kerosene. The goal of this study is to analyze the convection and conduction processes occurring in the combustion of tree ferns. It is conducted to explore the use of tree ferns as a raw material for the production of briquettes. The prototype briquette made using tree ferns is characterized by a honeycomb design with 14 holes and a diameter of 20 cm. It is made using a mixture of 20% adhesive and 80% tree fern charcoal. The various factors that influence the combustion process include the initial temperature, the pot wall temperature, the environmental temperature, and the moisture content of the briquette. Different instruments such as anemometer, an infrared thermometer, a stopwatch, and a moisture meter are also used in the study. The study revealed that the tree fern briquette made from 14 holes exhibited a convection heat transfer power of 4302.444watts and a conduction heat transfer power of 5106.5watts. The efficiency of the two processes allowed the briquettes to burn for about 2 hours and 30 minutes, and they could sustain a moisture content of 12%. The study indicates that tree ferns can serve as an energy source alternative to kerosene. This presents a sustainable and eco-friendly way of meeting energy demands